PHYSICO-CHEMICAL STUDIES OF DIFFERENT BER (ZIZYPHUS MAURITIANA LAMK.) GERMPLASM UNDER RAINFED CONDITIONS OF JAMMU - SHILPY KUMARI; DEEP JI BHAT,; V. K. WALI; PARSHANT BAKSHI; AMIT JASROTIA (The Bioscan, 2015)
An experiment was conducted during 2013-14 to study the physico-chemical characteristics of eight ber cultivars under rainfed conditions of Jammu. Among the physical characters, maximum fruit weight (19.07 g), fruit length (49.68 mm), fruit breadth (29.81 mm), fruit volume (17.50 cm3) was recorded in Sanaur-4 while, maximum specific gravity was recorded in Gola (1.38).The biochemical characters of different ber cultivars showed that Sanaur-4 recorded maximum TSS (15.750B) and TSS/acid ratio (40.38).Titratable acidity and Vitamin-C was found to be maximum (0.72 %) in Ranjari Selection-1 and Gola (106.80 mg/100g), respectively. Total sugars (12.30 %) and non-reducing sugars (8.41 %) were highest in Sanaur-4, whereas reducing sugars (4.35 %) was highest in Z.G-2. From the present investigation, it may be concluded that on the basis of quality attributes, Sanaur-4 was superior among all the cultivars and is the most promising ber cultivar for commercialization in rainfed conditions of Jammu.